1996
DOI: 10.1182/blood.v88.1.289.bloodjournal881289
|View full text |Cite
|
Sign up to set email alerts
|

Clonal circulating cells are common in plasma cell proliferative disorders: a comparison of monoclonal gammopathy of undetermined significance, smoldering multiple myeloma, and active myeloma

Abstract: The blood of most patients with active multiple myeloma (MM) contains cells related to the bone marrow tumor. However, identifying clonal cells in the blood of patients with monoclonal gammopathy of undetermined significance (MGUS) has been difficult. In this study, we analyzed blood mononuclear cells (BMNCs) from 16 patients with MGUS, 2 with amyloidosis, 8 with smoldering MM (SMM), 2 with indolent MM (IMM), and 15 with active MM using three different methods to detect and quantitate clonal cells, ie, immunof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
3
5

Year Published

1998
1998
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 37 publications
4
68
3
5
Order By: Relevance
“…As has been recently described [18], CD38 þþ CD45 ¹/dim cIg þ cells can be detected in the PB of MM patients by FCM analysis. However, their complete antigenic profile has not been determined [17,18]. Three-colour FCM analysis with the B-B4 (CD138) MoAb confirmed that all circulating CD38 þþ CD45 ¹/dim cells were positive for this antigen.…”
Section: Detection Of Malignant Plasma Cells In Pb From MM Patients: mentioning
confidence: 99%
See 1 more Smart Citation
“…As has been recently described [18], CD38 þþ CD45 ¹/dim cIg þ cells can be detected in the PB of MM patients by FCM analysis. However, their complete antigenic profile has not been determined [17,18]. Three-colour FCM analysis with the B-B4 (CD138) MoAb confirmed that all circulating CD38 þþ CD45 ¹/dim cells were positive for this antigen.…”
Section: Detection Of Malignant Plasma Cells In Pb From MM Patients: mentioning
confidence: 99%
“…In this regard, Jensen et al [16] have speculated that circulating CD19 þ CD11b þ cells appear to represent the myeloma precursor cells. Recently, Billadeau et al [17] and Witzig et al [18] found that circulating CD38 þþ , CD45 ¹/dim expressed monotypic cytoplasmic immunoglobulin (cIg) and showed characteristic plasma cell morphology. Nevertheless, these cells were not examined for their expression of B cell antigens and adhesion molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Progression to multiple myeloma in these six patients might be analogous to progression of MGUS to multiple myeloma. In both MGUS and AL, circulating clonal plasma cells have been identified in the peripheral blood 10. The number of such cells in AL and MGUS is significantly less than in overt multiple myeloma.…”
Section: Discussionmentioning
confidence: 99%
“…Ačkoliv se PC obvykle v periferní krvi nevyskytují, v případě ostatních MG mohou v nižším množství expandovat z KD do periferie jako cPC [9,10]. Přítomnost těchto klonálních cPC byla dokumentována u zhruba 70-84 % nově dia gnostikovaných pa cientů s MM a u > 90 % pa cientů v relapsu onemocnění [10][11][12][13][14].…”
Section: úVodunclassified